Digital forensics and cyber crime : 7th International Conference, ICDF2C 2015, Seoul, South Korea, October 6-8, 2015, revised selected papers /: 7th International Conference, ICDF2C 2015, Seoul, South Korea, October 6-8, 2015, revised selected papers. (2015) - Unknown
No abstract available